Locals’ Perception on Catfish Farming Cultivation to Prevent Stunting - Liufeto, Franchy Ch.; Manongga, Stefanus P.; Bunga, Markus (International Journal Labs, 2023)
Background: The catfish cultivating community plays an important role in fighting stunting in Timor Tengah Selatan, Kupang, and Manggarai Regencies. By encouraging people to increase their intake of protein from catfish, people increase their overall consumption of fish. Aim: This study aims to determine the perceptions of the village community towards the development of catfish farming to overcome stunting in Timor Tengah Selatan, Kupang, and Manggarai Regencies. Method: The method used in this study was a survey method, while the data collection technique in this study used a questionnaire and literature study. Findings: The results showed that in developing catfish farming, the positive response from the community towards freshwater fish in the Timor Tengah Selatan, Kupang, and Manggarai regions was significant. Of the 50 respondents, almost half said catfish farming was a good idea. As a result of poor marketing efforts and lack of public acceptance, many respondents believed the catfish industry would not be successful. More than half of the surveyed group or 61.67% believe that catfish marketing is inadequate. Moreover, 48.75% of respondents believe this industry will not be popular because people are not familiar with catfish and its related dishes.